Crop establishment, tillage and weed management techniques on weed dynamics and productivity of rice (Oryza sativa)-chickpea (Cicer arietinum) cropping system - MISHRA, J S; SINGH, V P; BHANU, CHANDRA; SUBRAHMANYAM, D (The Indian Journal of Agricultural Sciences, 2012)
A field study was conducted to study the effect of methods of rice establishment, tillage and weed management techniques in rice–chickpea cropping system. Treatments included four crop establishment techniques (transplanting, puddling and broadcasting sprouted rice seeds, i.e wet-seeding and dry seeding under conventional and zero tillage systems) in rice and two tillage (zero and conventional) and two weed control methods (weedy check and pendimethalin 1.0 kg/ha as pre-emergence + one hand weeding at 30 days after sowing) in succeeding chickpea. Rice field was infested with jungle rice [Echinochloa colona (L.) Link], Caesulia (Caesulia axillaris Roxb.), sessile joyweed [Alternanthera sessilis (L.) DC.], and rice flat sedge (Cyperus iria L.) and chickpea with wild oats (Avena ludoviciana Dur.) and toothed burclover (Medicago hispida Gaertn.). Results revealed that methods of rice establishment did influence the weed dynamics in rice– chickpea system. Mean yield of zero-till direct-seeded rice (3 262 kg/ha) was as good as that of puddle broadcast rice (3 343 kg/ha) and better than the transplanted rice (3 038 kg/ha). Effective weed control in preceding chickpea benefitted the succeeding rice crop. Methods of rice establishment and tillage did not influence the chickpea yield. Infestation of weeds caused 78.45% reduction in yield of chickpea. Maximum seed yield of chickpea (2 813 kg/ha) was noticed in pendimethalin followed by one HW under conventional tillage. Zero till direct-seeded rice followed by zero-till chickpea system was the best combination for maximizing system productivity, profitability and energy efficiency